2018
DOI: 10.1142/s0217979218503241
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic stability, half-metallic and optical nature of graphene-like Mn2 ZrZ (Z = Ge, Si): Ab initio study

Abstract: Half-metallic, optical and thermodynamic phase diagrams of two-dimensional Mn2ZrZ (Z = Ge, Si) have been calculated by density functional theory (DFT) framework with full-potential linear augmented plane-wave (FP-LAPW) method. The spin-polarized electronic computations show that these layers have metallic behavior with a spin polarization less than 100%. It is observed that with increasing thickness of the layers, both the thermodynamic and energy stabilities increased, and the graphene-like layers of Mn2ZrGe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…In their study, they found small indirect band gap in majority spin channel of 0.505 eV and 0.278 eV for Mn 2 ZrSi and Mn 2 ZrGe, respectively. Similar effects were reported by Anjami et al, 15 while they investigated the graphene-like layers of Mn 2 ZrGe and Mn 2 ZrSi with a thickness of 7.6955 Å and 7.551 Å, respectively, which are found to be thermodynamically stable, highly anisotropic and ferromagnetic in nature. They also investigated that the optical responses of Mn 2 ZrGe and Mn 2 ZrSi are effective near infrared region.…”
supporting
confidence: 82%
“…In their study, they found small indirect band gap in majority spin channel of 0.505 eV and 0.278 eV for Mn 2 ZrSi and Mn 2 ZrGe, respectively. Similar effects were reported by Anjami et al, 15 while they investigated the graphene-like layers of Mn 2 ZrGe and Mn 2 ZrSi with a thickness of 7.6955 Å and 7.551 Å, respectively, which are found to be thermodynamically stable, highly anisotropic and ferromagnetic in nature. They also investigated that the optical responses of Mn 2 ZrGe and Mn 2 ZrSi are effective near infrared region.…”
supporting
confidence: 82%